Analysis Of Profits And Feasibility Of The Tempe Household Tempe Crafts Manufacturer In Lamper Tengah Village, Semarang Selatan District - Meiriyanti, Rita; Rinawati, Tri; Hartoto, Witjaksono Eko (Universitas Semarang, 2018)
A small industry has a strategic role in driving the economy. One of the potential small industries to be developed is the tempe industry. This study aims to analyze the benefits and feasibility tempe crafts manufacturer in Lamper Tengah Village, Semarang Selatan District which is the largest tempe industry area in Semarang City so that the results of the analysis can be taken into consideration to further develop their business.This research design uses quantitative methods. This research is a case study so business owners making tempeh in Semarang City is used as a source to obtain information needed in research. The data used are primary and secondary. Data collection techniques carried out by interview, observation, and recording. Data obtained analyzed using profit analysis Ï€ = TR-TC and to find out business feasibility using the formula R / C Ratio.The results of this study indicate that the average total cost incurred by tempe producers in Lamper Tengah Village per month is Rp 16,916,210.70. The average amount of tempe produced was 18,108 packs with an average price of Rp. 2,500, so that the average monthly income earned by tempe craftsmen is Rp 45,270,556 and the average profit gained is Rp 28,354,355. The business of making soybean tempe has an efficiency value of 2.68, meaning that every one rupiah the costs incurred will get an income of 2.68 times the cost incurred, then the tempe industry business in Lamper Tengah Village is feasible to continue and can even be invested in industrial development the tempe.Keywords: Profit, Business Feasibility, Tempe Crafts Manufacturer